DIGITALIZATION OF ISLAMIC MICROFINANCE INSTITUTIONS: OPPORTUNITIES, CHALLENGES, AND ECONOMIC IMPLICATIONS FOR THE MUSLIM COMMUNITY - Khoirudin; Juliana (IZZI: Jurnal Ekonomi Islam, 2025)
This study explores the digital transformation of Islamic Microfinance Institutions (LKMS) by analyzing the forms of innovation, strategic opportunities, implementation challenges, and socio-economic impacts. Using a qualitative library research method, this paper synthesizes findings from academic literature, official reports, and sharia-compliant fintech developments to evaluate how digitalization aligns with the objectives of maqashid shariah. The results show that LKMS have begun integrating digital solutions such as mobile apps, cloud-based accounting, and blockchain-based systems to enhance service efficiency, accessibility, and transparency. Digital transformation has increased operational capacity and outreach while promoting economic inclusion among marginalized communities. However, the study also highlights several challenges, including infrastructure limitations, digital illiteracy, and sharia compliance concerns. The conclusion emphasizes the need for institutional and regulatory support to optimize the benefits of digital innovation within Islamic ethical finance. Further empirical research is suggested to explore the effectiveness of digital platforms in realizing sustainable economic empowerment aligned with sharia principles.